The Effect of Work From Home (WFH) and the Work Environment During the Covid-19 Pandemic on ASN Work Productivity at the Bengkulu Province P3ppkb Office (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange for the 20218-2020 - Gempo Priharto; Nia Indriasari; Siti Hanila (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the work from home and work environment during the Covid-19 pandemic on the work productivity of ASN at the P3APPKB Office of Bengkulu Province. The population in this study amounted to 80 ASN with a saturated sampling technique, where all members of the population were sampled. Work From Home (X1) had a positive and significant effect on Productivity during the COVID-19 Pandemic Period ASN Work at the P3APPKB Office of Bengkulu Province. This can be seen from the significant Work From Home (X1) 0.012 < 0.05 and the value of t table = t (a/2 ;nk-1) = t (0.025 ; 77 = 1.994 means the value of tcount is greater than ttable 2.574 > 1.994 then H0 rejected and H1 accepted. Work Environment Variable (X2) had a positive and significant effect on Productivity during the COVID-19 Pandemic Period of ASN Work at the Bengkulu Province P3APPKB Office. 0.124 > 0.05 and value tcount = t (a/2 ;nk-1) = t (0.025; 77 = 1.994 means the value of tcount is greater than ttable 1.555 < 1.994 then H0 is rejected and H1 is accepted. Test F: F table = F (k;nk) =F (2;80-2;78 + 3, 11. it can be seen that the value of Fcount is 4.996 with the value of Ftable is 3.11 so that the value of Fcount and Ftable or 4.996 > 3.11, and a significant level of 0.009 < 0.05 then H0 is rejected and H3 is accepted, it can be concluded that the Work Form Home variable (X1 ) and the Work Environment (X2) simultaneously affect productivity during the COVID-19 Pandemik Period of ASN Work at the P3APPKB Office of Province B engkulu. By using multiple linear regression and the results of the study indicate that there is an effect of the variable Work From Home (X1) and the work environment (X2) partially influencing the work productivity of ASN in the P3APPKB Office of Bengkulu Province. Work From Home (X1) and Work Environment (X2) Simultaneous effect on productivity (Y) is 92%.